1996
DOI: 10.1111/j.1749-7345.1996.tb00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxin Production by a Chloromonad Fibrocapsa japonica (Raphidophyceae)

Abstract: The ichthyotoxicity and toxin composition of a red-tide producing chloromonad Fibrocupsu juponicu (Toriumi and Takano) were examined. The flagellate showed the highest toxicity in mid-logarithmic phase and the lowest in the stationary phase with increased number of spherical-shaped cells. Five neurotoxic components, FjTx-I, FjTx-11, FjTx-IIIa, FjTx-IIIb and FjTx-IV, which corresponded to brevetoxin components, PbTx-1, PbTx-2, PbTx-9, PbTx-3 and oxidized PbTx-2 were tentatively identified from analysis of F. ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 19 publications
3
49
3
Order By: Relevance
“…We found that both thecate and athecate heterotrophic dinoflagellates in this study readily ingest prey and exhibit positive growth when feeding on monocultures of Fibrocapsa japonica, which has been reported to produce a potent neurotoxin (Khan et al 1996b). Little is known about the toxic action of F. japonica.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…We found that both thecate and athecate heterotrophic dinoflagellates in this study readily ingest prey and exhibit positive growth when feeding on monocultures of Fibrocapsa japonica, which has been reported to produce a potent neurotoxin (Khan et al 1996b). Little is known about the toxic action of F. japonica.…”
Section: Discussionmentioning
confidence: 68%
“…Little is known about the toxic action of F. japonica. The toxin has been classified as a neurotoxin similar to brevetoxin, but with a higher toxicity (Khan et al 1996b, Nannen 1998. Moreover, Oda et al (1997) demonstrated that raphidophycean flagellates (including F. japonica) may produce substantial quantities of toxic oxygen radicals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brevetoxins (BTX) production has been reported for some isolates of all raphidophyte genera (Khan et al 1996(Khan et al ,1997(Khan et al ,2001) and there is a need for rapid and accurate monitoring of water samples for areas considered at risk, both to ensure the health of cultured fish stock and to protect shellfish from potential BTX contamination. No New Zealand isolates of any raphidophytes tested to date, including the Chattonella species, have been shown unequivocally to produce BTX (Paul McNabb, Biotoxin Laboratory, Cawthron Institute, New Zealand, pers.…”
Section: Introductionmentioning
confidence: 99%